VILLAGE FUNDS MANAGEMENT IN THE DEVELOPMENT OF SUMBEREJO VILLAGE, BATUWARNO SUB-DISTRICT, WONOGIRI DISTRICT - Saraswati, Yudhistira; Wastutiningsih, Sri Peni; Priyotamtama, P Wiryono (J-3P (Jurnal Pembangunan Pemberdayaan Pemerintahan), 2023)
Dana Desa or village funds have contributed in increasing the village's infrastructure development and community empowerment. Therefore, it must be managed and utilized appropriately. The purpose of this study is to analyze the management of the village funds in Sumberejo Village, Batuwarno District, Wonogiri Regency. This research uses a descriptive qualitative approach. Meanwhile, data collection techniques are gained through in-depth interviews, observation, and study literature. The results show that the management of village funds was designed to meet the needs and priorities of village development policies. These policies are contained in the RPJMDesa. The community manages infrastructure development through a self-management system and involves third parties on a contractual basis. On the other hand, business units manage community empowerment activities at BUMDesa. The monitoring stage only refers to the budget via the APBDesa Accountability Report, not the process. Keywords: Village Funds, Management, POAC, RPJMDesa